Tracking the correlation of mineral intakes among family pairs over nine years: a longitudinal study - Farshad Teymoori; Mahdi Akbarzadeh; Niloufar Saber; Mitra Kazemi Jahromi; Ebrahim Mokhtari; Parisa Riahi; Hossein Farhadnejad; Hamid Ahmadirad; Asiyeh Sadat Zahedi; Sajedeh Masjoudi; Danial Habibi; Maryam Zarkesh; et al. (BMC Nutrition, 2025)
Abstract Background This study aimed to assess possible changes in mineral intake correlation between family pairs over time. Mineral intake was measured using a food frequency questionnaire. Methods FCOR command of the Statistical Analysis for Genetic Epidemiology software was used to determine the correlation coefficients of minerals in relative pairs. Our first analysis was conducted on adults (n = 748) who had four complete dietary and familial data on the third to sixth surveys of the Tehran Lipid and Glucose Study. In addition, we assessed respectively the 3-year, 6-year, and 9-year changes in mineral correlations among populations with n = 1773, n = 1672, and n = 1352 samples with two mineral intake measurements. Results Most of the mineral correlations among various pairs were found to be in the same direction in both four and two measurement analyses. Among the mother-daughter and brother-sister pairs, there was a decreasing correlation for all minerals over time. In father-daughter, we observed decreasing or regression to the mean of correlations. For father-son and spouse pairs, the correlations between minerals showed a decreasing trend or regression to the mean over time, whereas increased for sodium in the father-son and phosphorus in the spouse pair. For mother-son and brother-brother pairs, iron intake correlation increased and other minerals correlations generally showed a decreasing trend or regression to the mean. Among sister-sister pairs, the correlation of calcium and phosphorus decreased, however, the correlation of chromium, selenium, sodium, and potassium increased. Conclusion Our study revealed a decreasing trend in correlation or regression towards the mean over time for most minerals in family pairs.